Fabrication and Evaluation of Electrospun Silk Fibroin/Halloysite Nanotube Biomaterials for Soft Tissue Regeneration - Mohammadzadehmoghadam, Soheila; LeGrand, Catherine F; Dong, Yu; Wong, Chee-Wai; Kinnear, Beverley F; Dong, Roger; Coombe, Deirdre R (MDPI AG, 2022)
The production of nanofibrous materials for soft tissue repair that resemble extracellular matrices (ECMs) is challenging. Electrospinning uniquely produces scaffolds resembling the ultrastructure of natural ECMs. Herein, electrospinning was used to fabricate Bombyx mori silk fibroin (SF) and SF/halloysite nanotube (HNT) composite scaffolds. Different HNT loadings were examined, but 1 wt% HNTs enhanced scaffold hydrophilicity and water uptake capacity without loss of mechanical strength. The inclusion of 1 wt% HNTs in SF scaffolds also increased the scaffold’s thermal stability without altering the molecular structure of the SF, as revealed by thermogravimetric analyses and Fourier transform infrared spectroscopy (FTIR), respectively. SF/HNT 1 wt% composite scaffolds better supported the viability and spreading of 3T3 fibroblasts and the differentiation of C2C12 myoblasts into aligned myotubes. These scaffolds coated with decellularised ECM from 3T3 cells or primary human dermal fibroblasts (HDFs) supported the growth of primary human keratinocytes. However, SF/HNT 1 wt% composite scaffolds with HDF-derived ECM provided the best microenvironment, as on these, keratinocytes formed intact monolayers with an undifferentiated, basal cell phenotype. Our data indicate the merits of SF/HNT 1 wt% composite scaffolds for applications in soft tissue repair and the expansion of primary human keratinocytes for skin regeneration.